The Applicability of an Extended Technology Acceptance Model for Electronic Medical Records in Jordan - Khorma, Ola Taiseer (2012)
Electronic Medical Record (EMR) is able to reduce medical errors, cost and time for data storage and retrieval. It is also capable of improving information workflow and work efficiency. Despite the benefits of using EMR, low acceptance among doctors is a common problem in many countries including Jordan. The present acceptance studies of EMR have yet to integrate Self-Efficacy and Perceived Behavioural Control as individual capabilities that influence Perceived Usefulness and Perceived Ease of Use among doctors in Jordan. Therefore, the main objective of this study is to develop an extended Technology Acceptance Model that measures doctor’s acceptance of EMR in private hospitals in Jordan by incorporating three perspectives: individual capabilities, technological, and behavioural. Self-Efficacy and Perceived Behavioural Control were added as factors of individual capabilities perspective while Perceived Usefulness and Perceived Ease of Use were included as technological perspective, and Behavioural Intention as a factor for behavioural perspective. This study applied a Cross-Sectional survey, and used the Random Sampling technique to select the sample in the targeted hospitals in Jordan. This study also used self-administered questionnaires. In validating the model, the data were analysed using the Structural Equation Model, based on the Partial Least Square approach. The findings indicated that Perceived Usefulness has a positive direct effect on Behavioural Intention to use EMR, and Self-Efficacy has a direct effect on Perceived Ease of Use. Furthermore, Perceived Behavioural Control has a direct positive effect on Perceived Usefulness and Perceived Ease of Use. These outcomes could assist the healthcare top management in restructuring their strategic planning to improve the EMR implementation. In future, this model can be further tested and extended in other Information Technology (IT) applications, which means that this model can be generalized into the IT domain.